Membangun Kesadaran Sejak Dini: PHBS dan Kegiatan Pengolahan Limbah Organik pada Siswa SDN 1 Jetis Kabupaten Bondowoso - Mutawakkil, Muhammad Afif; Umami, Fajar Fairi; Karin, Sheila Aulia Ismi; Rendratama, Alvian; Kurniawan, Bintang Indra; Pratama, Muhammad Reyhan Iwan; Puspito, Agung Nugroho (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Schools are strategic environments for instilling clean and healthy living habits (PHBS) in elementary school children, which significantly influence their physical, mental, and social development. This study aims to enhance the awareness and understanding of 5th-grade students at SDN 1 Jetis Bondowoso regarding the importance of personal hygiene, environmental cleanliness, and recycling skills as part of a healthy and environmentally friendly lifestyle. The method used is a social project research with a descriptive qualitative approach, involving interactive educational activities such as health material delivery, recycling skill practice, and physical activities conducted over three sessions. The results show an increase in students' knowledge and awareness of PHBS as well as practical abilities in waste management through recycling. These activities not only foster healthy living habits but also build students' environmental care and independence. This program is expected to serve as a sustainable health promotion education model in elementary schools.